Perception of static eye gaze direction facilitates subsequent early visual processing - Schuller, Anne-Marie; Rossion, Bruno (Clinical neurophysiology, 2004)
Objective: Using event-related potentials (ERPs), it has been recently shown that a reflexive shift of attention following the observation of a dynamic eye gaze cue enhances and speeds up early visual processing of a target presented at the gazed-at location. Here we investigate whether similar early sensory modulations are also elicited by static gaze cues, or if previously described attentional effects were caused mainly by visual motion cues and not by eye gaze direction per se. Furthermore, we explore if these possible attentional orienting effects reflect facilitation of the processing of cued stimuli, inhibition of the unattended stimuli, or both. Methods: Subjects were presented with a face looking to the right or left visual field (VF), or straight away, before the occurrence of a lateralized target to detect. There were 3 conditions in this nonpredictive cueing task: (1) target presented in the VF indicated by the eye gaze direction (congruent); (2) opposite to the eye gaze direction (incongruent); or (3) preceded by a straight gazing face (neutral). Results: Subjects were faster at detecting congruently than incongruently and neutrally cued targets. Facilitation effects were observed on early ERP components: the occipital P1 and occipito-temporal N1 components were speeded up as early as ∼100 ms following stimulus onset (P1), and enhanced (P1 and N1) in response to congruent trials, particularly in the right hemisphere. Conclusions: Spatial attention triggered by static eye gaze direction produces response facilitations – predominantly lateralized to the right hemisphere – from the early sensory stages of visual processing. Significance: This study provides the first evidence of a speeding up and amplification of early visual processing following attention triggered by static eye gaze perception.